An outsider's inside view of ethnic entrepreneurship. Issue 1 (11th July 2016) - McPherson, Mark
Abstract : Purpose: This paper aims to critically reflect upon the qualitative research strategy adopted by an outsider investigating business practices between first and second-generation South Asian entrepreneurs. The paper presents, explains and justifies the methodological design and outsider strategy used to help overcome a number of operational research issues. In addition, for those considering the use of qualitative methodology for similar research, practical advice is offered to researchers whom do not share the same ethnicity as the informants under investigation. Design/methodology/approach: To implement an outsider strategy, the methodological design draws its theoretical underpinning via a phenomenological paradigm. Issues appertaining to sample design, negotiating access, adopted research instruments are examined, and their uses to overcome potential operational issues justified. Findings: The complexities, difficulties and successes of an outsider looking in are highlighted. Evident is the impact of personal and structural power relations between researcher and interviewee, as well as potential research problems as a result thereof. The paper stresses the need to ensure the preservation of researcher integrity, credibility and confidentiality, as he/she will encounter situations wherein he/she will be tested to the fullest. Research limitations/implications: The research environment within the Greater London area where the respondents are located may not be as generalisable when compared with other parts of the UK and ethnic entrepreneurs therein. Originality/value: The paper presents an evaluation of a qualitative research strategy used by an outsider to gain an inside view of ethnic entrepreneurship.